Gender and violence in historical and contemporary perspectives: situating India - Atwal, Jyoti; Fleßenkämper, Iris (Routledge, 2020)
"This volume examines gender-related violence regarding specific cultural and regional conditions. Using an interdisciplinary perspective, it discusses broader historical and contemporary developments which trigger violence paying attention to the social conditions, practices, discourses, and (cultural) experiences of gender-related violence. It situates gender-specific violence in historical and current constellations to reveal consistencies and developments; to explore and interpret similarities and differences; and to identify social causes of potential conflict. It focuses on sexual violence, especially on its function in establishing and distinguishing group identities. The book also studies the influence of physical violence on the stabilization or destabilization of traditional gender roles, particularly in the private sphere of marriage and family - a sphere that is considered a "starting-point for social change" in India today. The chapters also investigate the forms and mechanisms of political, economic or institutional violence in the legitimation or de-legitimation of traditional gender patterns. They also address issues of violence towards transgender people, disabled women, and minority women. This book will be useful for scholars and researchers of gender studies, history, women studies, sociology and political science"--